Bioassay-Guided Isolation of Sesquiterpene Coumarins from Ferula narthex Bioss: A New Anticancer Agent - Alam, Mahboob; Khan, Ajmal; Wadood, Abdul; Khan, Ayesha; Bashir, Shumaila; Aman, Akhtar; Jan, Abdul Khaliq; Rauf, Abdur; Ahmad, Bashir; Khan, Abdur Rahman; Farooq, Umar (Frontiers in Pharmacology, 2016)
The main objective of cancer management with chemotherapy (anticancer drugs) is to kill the neoplastic (cancerous) cell instead of a normal healthy cell. The bioassay-guided isolation of two new sesquiterpene coumarins (compounds 1 and 2) have been carried out from Ferula narthex collected from Chitral, locally known as “Raw”. Anticancer activity of crude and all fractions have been carried out to prevent carcinogenesis by using MTT assay. The n-hexane fraction showed good activity with an IC50 value of 5.434 ± 0.249 µg/mL, followed by crude MeFn extract 7.317 ± 0.535 µg/mL, and CHCl3 fraction 9.613 ± 0.548 µg/mL. Compounds 1 and 2 were isolated from chloroform fraction. Among tested pure compounds, compound 1 showed good anticancer activity with IC50 value of 14.074 ± 0.414 µg/mL. PASS (Prediction of Activity Spectra) analysis of the compound 1 was carried out, in order to predicts their binding probability with anti-cancer target. As a results the compound 1 showed binding probability with human histone acetyltransferase with Pa (probability to be active) value of 0.303. The compound 1 was docked against human histone acetyltransferase (anti-cancer drug target) by using molecular docking simulations. Molecular docking results showed that compound 1 accommodate well in the anti-cancer drug target. Moreover the activity support cancer chemo preventive activity of different compounds isolated from the genus Ferula, in accordance with the previously reported anticancer activities of the genus.